The Development of Soft Skills in the Provision of Competitiveness of Graduates - Shaulska, L.V.; Sereda, G.V.; Shkurat, M.Y. (Економічний вісник Донбасу, 2015)
The most strong competition in the labor market is in the segment of young people without work experience. The paper is devoted to the development of perspective directions of the enhance the competitiveness of specialists with higher education, developing their socio-emotional, cognitive skills - "soft skills". On the basis of the analysis of the definition "competence" the authors substantiate the necessity of development within higher education personal characteristics (socio-emotional and cognitive skills) of future graduates in line with labour market needs. It provides the experience of leading Ukrainian universities in the creation and introduction in educational process of special training course on "Soft skills" aimed to develop socio-emotional and cognitive abilities of students. In the paper it proposed the main directions of improving the system of training the specialists for the enhance their competitiveness in the labour market: use competence approach to the development of standards for higher education; the introduction of continuous monitoring of the needs of employers in determining the competence of professionals; reorientation of educational content (educational and vocational programs, work programs of disciplines) on the characteristics of effective learning in terms of competences formed; the inclusion in curricula of preparation of specialists of the disciplines contributing to the development of cognitive and socioemotional skills; development of tools for inspecting the degree of formation of cognitive and socioemotional skills (soft skills). Конкуренція на ринку праці є найбільш напруженою в сегменті молоді без досвіду роботи. Роботу присвячено розробці перспективного напрямку підвищення конкурентоспроможності фахівців з вищою освітою - розвитку їх соціо-емоційних, когнітивних здібностей - «soft skills». На основі аналізу сутності поняття «компетенції» авторами обґрунтовано необхідність розвитку в рамках вищої освіти особистісних характеристик (соціо-емоційних та когнітивних навичок) майбутніх випускників у відповідності до потреб ринку праці. Наводиться досвід розробки провідними українськими університетами та впровадження в навчальний процес спеціального тренінгового курсу «Soft skills», який спрямований на розвиток соціо-емоційних та когнітивних здібностей студентів. В статті запропоновані основні тенденції удосконалення системи підготовки фахівців в напрямі підвищення їх конкурентоспроможності на ринку праці: використання компетентісного підходу до розробки стандартів вищої освіти; впровадження постійного моніторингу потреб роботодавців в певних компетенціях фахівців; переорієнтація змісту освіти (освітньо-професійних програм, робочих програм дисциплін) на результативні характеристики навчання в термінах сформованих компетенцій; включення в навчальні плани підготовки фахівців дисциплін, що сприяють розвитку когнітивних та соціо-емоційних вмінь; розробка інструментарію перевірки ступеня сформованості когнітивних та соціо-емоційних вмінь (soft skills). Конкуренция на рынке труда является наиболее напряженной в сегменте молодежи без опыта работы. Работа посвящена разработке перспективного направления повышения конкурентоспособности специалистов с высшим образованием - развитию их социо-эмоциональных, когнитивных способностей («soft skills»). На основе анализа сущности понятия «компетенции» авторами обоснована необходимость развития в рамках высшего образования личностных характеристик (социо-эмоциональных и когнитивных навыков) будущих выпускников в соответствии с потребностями рынка труда. Приводится опыт разработки ведущими украинскими университетами и внедрения в учебный процесс специального тренингового курса «Soft skills», который направлен на развитие социо-эмоциональных и когнитивных способностей студентов. В статье предложены основные тенденции совершенствования системы подготовки специалистов в направлении повышения их конкурентоспособности на рынке труда: использование компетентностного подхода к разработке стандартов высшего образования; внедрение постоянного мониторинга потребностей работодателей в определенных компетенциях специалистов; переориентация содержания образования (образовательно-профессиональных программ, рабочих программ дисциплин) на результативные характеристики обучения в терминах сформированных компетенций; включение в учебные планы подготовки специалистов дисциплин, способствующих развитию когнитивных и социо-эмоциональных умений; разработка инструментария проверки степени сформированности когнитивных и социо-эмоциональных умений (soft skills).